CoQ10 and Cognition a Review and Study Protocol for a 90-Day Randomized Controlled Trial Investigating the Cognitive Effects of Ubiquinol in the Healthy Elderly - Stough, Con; Nankivell, Madeleine; Camfield, David A.; Perry, Naomi L.; Pipingas, Andrew; Macpherson, Helen; Wesnes, Keith; Ou, Ruchong; Hare, David; de Haan, Judy; Head, Geoffrey; Lansjoen, Peter; et al. (Frontiers in Aging Neuroscience, 2019)
Introduction: With an ageing population there is an important need for the development of effective treatments for the amelioration of cognitive decline. Multiple mechanisms underlie age-related cognitive decline including cerebrovascular disease, oxidative stress, reduced antioxidant capacity and mitochondrial dysfunction. CoQ10 is a novel treatment which has the potential to improve brain function in healthy elderly populations due to established beneficial effects on mitochondrial function, vascular function and oxidative stress. Methods and Analysis: We describe the protocol for a 90-day randomized controlled trial which examines the efficacy of Ubiquinol (200mg/day) versus placebo for the amelioration of cognitive decline in a healthy (non-demented) elderly sample, aged 60 years and over. The primary outcome is the effect of Ubiquinol at 90-days compared to baseline on CogTrack composite measures of cognition. Additional cognitive measures, as well as measures of cardiovascular function, oxidative stress, liver function and mood will also be monitored across 30-, 60- and 90- day time points. Data analyses will involve repeated measures analysis of variance. Discussion: This study will be the first of its kind to provide important clinical and mechanistic data regarding the efficacy of Ubiquinol as a treatment for age-related cognitive decline in the healthy elderly with important implications for productivity and quality of life within this age group. Ethics and Dissemination: The study has been approved by the institutional ethics committee and all participants will provide written informed consent. Additionally, the trial has been registered with the Australian and New Zealand Clinical Trials Registry (ANZCTRN12618001841268).